Effects of deep frying and baking on the quality attributes, water distribution, and flavor characteristics of duck jerky - Pei, Yamin; Guo, Xingyue; Shu, Xionghui; Han, Yahong; Ai, Youwei; Wang, Hongxun; Hou, Wenfu (Frontiers in Nutrition, 2024)
The nutritional value of duck meat is well acknowledged due to its low cholesterol and high protein content. Nevertheless, the impacts of deep-frying and baking on its quality characteristics are not extensively documented in literature. The objective of this study is to examine the effects of deepfrying, pre-boiling-deep-frying, baking, and pre-boiling-baking on the quality attributes, water distribution, microstructure, and flavour characteristics of duck jerky. The findings revealed that the deep-frying group had better quality attributes than the baking, pre-boiling-deep-frying, and preboiling-baking groups. The deep-fried duck jerky had a higher a* value (4.25) and a lower b* value (5.87), with a more appropriate texture profile, and had the highest comprehensive impression score (5.84). Moreover, the drying rate was faster, and the intensity of the free water and oil signal was significantly elevated in the deep-frying group. The microstructure results indicated that the muscle fibres in the deep-frying group were closely packed, whereas those in the baking group were relatively loose. Furthermore, the GC-IMS test revealed that the deep-fried duck jerky had a wider range of volatile flavour compounds, including 11 unique compounds that were only found in this particular product.